Designing for playfulness through compassion: design for advanced dementia. Issue 1 (2nd January 2019) - Treadaway, Cathy; Fennell, Jac; Taylor, Aidan; Kenning, Gail
Abstract: Those who have the greatest need for excellent design are often the most vulnerable in society. These people may find it difficult or impossible to articulate their design requirements due to physical, sensory or memory impairment as a result of accident or disease. Finding ways to understand the challenges they face moment-by-moment and day-by-day is vital. Empathic and compassionate approaches that place an individual central to the design process can inform outcomes that significantly benefit the user as well as those that care for them. This paper presents research that aims to support the wellbeing of people living with advanced dementia by designing to promote pleasure and positive emotion. The LAUGH project is a recently completed international three-year UK AHRC funded design research project. Outputs from the study include a collection of playful objects, designed to provide comfort, pleasure and fun. This paper describes the research process underpinning the development of the designs and the Compassionate Design methodology that has informed the work. The design narratives behind the playful objects will be explained in relation to the three key themes of Compassionate Design, which stress the importance of personalization, sensory stimulation and maintaining connections between people and the world.